2019
DOI: 10.2196/13593
|View full text |Cite
|
Sign up to set email alerts
|

Using Web-Based Pin-Drop Maps to Capture Activity Spaces Among Young Adults Who Use Drugs in Rural Areas: Cross-Sectional Survey

Abstract: BackgroundEpicenters of harmful drug use are expanding to US rural areas, with rural young adults bearing a disproportionate burden. A large body of work suggests that place characteristics (eg, spatial access to health services) shape vulnerability to drug-related harms among urban residents. Research on the role of place characteristics in shaping these harms among rural residents is nascent, as are methods of gathering place-based data.ObjectiveWe (1) analyzed whether young rural adults who used drugs answe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…The final sample thus included 151 valid surveys. More details on fraud detection can be found elsewhere [36,39].…”
Section: Overviewmentioning
confidence: 99%
“…The final sample thus included 151 valid surveys. More details on fraud detection can be found elsewhere [36,39].…”
Section: Overviewmentioning
confidence: 99%
“…Though the War on Drugs of the 1980s and 1990s was waged against urban communities of color as a mechanism to maintain racial/ethnic and class hierarchies in post-Jim Crow era (Weiss Riley et al, 2018), it has since travelled with the burgeoning opioid epidemic into predominately White, non-Hispanic rural areas, transforming these risk environments. National data reveal that rural counties are experiencing greater increases in arrest rates than their more urbanized counterparts; a study in these same five counties by Cooper et al (2019) found that 39.7% of PWUO or PWID had a history of arrest. In this qualitative sample, young adult PWUO -residents of rural counties where >95% of residents were non-Hispanic White -reported significant police activity and fear of arrest and incarceration.…”
Section: Discussionmentioning
confidence: 99%
“…Thereafter, staff members contacted participants suspected of fraud to inform them that their entry was flagged and to request they contact staff members to verify their entry to receive compensation, although none did. Staff members identified an additional 18 entries as fraudulent using strategies (described elsewhere 35 ) that were informed by a fraud-detection algorithm used previously in online research. 36 Staff members identified these entries after data collection had ended; as such, these participants were not contacted.…”
Section: Discussionmentioning
confidence: 99%
“…Demographic and behavioral characteristics of the final valid sample (n = 151) are described elsewhere. 35 Recruitment method yield and peer referral. We used SPSS version 25 (IBM Corp) to calculate descriptive statistics of the numbers of online screening survey entries, eligible entries, and complete and nonfraudulent eligible surveys for each recruitment method.…”
Section: Discussionmentioning
confidence: 99%